Examining the influence of e-learning readiness on student satisfaction and motivation towards online learning - Nur Nasyirah Roslan
E-Iearning is learning utilizing electronic technologies to access educational curriculum outside of a traditional classroom. E-Iearning conducted via electronic media, typically on the Internet. The aim of the study is to investigate the influence of e-learning readiness on student satisfaction and motivation towards online learning. E¬learning are one of the criteria discussed in Pelan Pembangunan Pendidikan Malaysia 2015-2025 (Pendidikan Tinggi). The 9th pillar are application of e-learning in globalization level. The readiness of teachers and learners for E-Iearning has been discussed in several studies in the last decade. The studies showed that results related to the different aspect of E-Iearning readiness can vary over time, among institution or instruments that were used for the assessment. The study was based on a sample gathered from undergraduate students in Universiti Sultan Zainal Abidin, using a self¬administered questionnaire. Of the total 350 questionnaires distributed, 312 returned the questionnaire, giving a response rate of 89%. Partial Least Squares (PLS) approach was used to analyze the data and to test the hypotheses. The results suggested that internet self-efficacy, online communication self-efficacy, self-directed learning towards motivation and computer self-efficacy, internet self-efficacy, online communication self-efficacy and self-directed learning variable towards satisfaction has no strong relation towards e-learning readiness among students compared to computer self-efficacy, perceived usefulness, and e-learning motivation towards motivation and perceived usefulness and e-learning motivation towards satisfaction variables. Therefore, the findings suggested that supported hypothesis play a significant role in encouraging e-learning readiness among undergraduates' students. This study highlights on the most factors that influence e-learning readiness among the undergraduate students in Universiti Sultan Zainal Abidin as well as provides some suggestions regarding the future research for knowledge sharing. Parents and academic institution need to play and important role in establishing students' e¬learning motivation by allowing them to explore more information through online. Lecturers may also creating an environment where students are keen to share knowledge through online and celebrate the benefits of learning through online, respectively.